Volume 5: Manufacturing Materials and Metallurgy; Ceramics; Structures and Dynamics; Controls, Diagnostics and Instrumentation; 1989
DOI: 10.1115/89-gt-213
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetic Damper for First Mode Vibration Reduction in Multimass Flexible Rotors

Abstract: Many r o t a t i n g machines such as compressors, t u r b i n e s and pumps have l o n t h i n s h a f t s with r e s u l t i n g v i b r a t i o n problems. They would b e n e f i t from a d d i t i o n a f damping n e a r t h e c e n t e r of t h e s h a f t . t h e s e machines because t h e y can o p e r a t e i n t h e working f l u i d environment u n l i k e conventional b e a r i n g s . This paper d e s c r i b e s an experimental test r i g which was set up with a long t h i n s h a f t and s e v e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Nikolajsen et al (1979) demonstrated the use of AMDs for the suppression of vibrations in long transmission shafts. Kasarda et al (1990) demonstrated experimentally that the location of the damper in a multimass rotor plays an important role in its effectiveness because of the rotor mode shapes, and reported that significant reductions of up to 88% in synchronous vibrations at the first and second critical speeds were attainable. The work presented in this paper expands on previous studies and shows experimental results demonstrating the effectiveness of an AMD to reduce subsynchronous vibrations, such as those caused by instability mechanisms, in a single-disk flexible rotor.…”
Section: Mechanics Research Communicationsmentioning
confidence: 97%
“…Nikolajsen et al (1979) demonstrated the use of AMDs for the suppression of vibrations in long transmission shafts. Kasarda et al (1990) demonstrated experimentally that the location of the damper in a multimass rotor plays an important role in its effectiveness because of the rotor mode shapes, and reported that significant reductions of up to 88% in synchronous vibrations at the first and second critical speeds were attainable. The work presented in this paper expands on previous studies and shows experimental results demonstrating the effectiveness of an AMD to reduce subsynchronous vibrations, such as those caused by instability mechanisms, in a single-disk flexible rotor.…”
Section: Mechanics Research Communicationsmentioning
confidence: 97%
“…Some of the fundamental work done by Alliare, Humphris et al, [1,2,3,4,7,8,9,11], gave useful experimental insight into the contribution of the bearing stiffness and damping to the general rortor dynamic behaviour. Results of their experimental work with different circuit band widths were also compared in terms of the achieved stability regions.…”
Section: Introductionmentioning
confidence: 99%
“…It was found in this work (Kasarda et al, 1990;Nikolajsen et al, 1979) that a very substantial reduction in vibration amplitudes could be achieved through the used of these "Active Magnetic Dampers" (AMDs).…”
Section: Introductionmentioning
confidence: 99%